A CASE OF POLY-INFECTION WITH cUTI AND GRADE III BED SORE IN TYPE II DIABETES TREATED WITH NEW ANTIBIOTIC ADJUVANT ENTITY: A CASE REPORT - Verma, Suneet Kumar (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Critically ill patients with diabetes are commonly associated with urinary tract infection and high-risk of bed sores or pressure ulcers. We report a case of 72 years male patient, a known case of meningoencephalitis, treated 1 month back. He arrived to our emergency department, with chief complaints of fever and increased drowsiness since 10-12 days. Based on the initial examination, the patient was empirically managed with intravenous meropenem 1 g every 8 hrs. However, due to patient poor clinical response antibiotic therapy was switched to Elores 1.5 g B.D dose with 90 minutes infusion. The patient received Elores therapy for 7 days, based on lab reports and general condition, he was put on oral antibiotics and shifted to ward. On the 5 day of post ward transfer, the patient developed mild pleural effusion with mild hypokinesis, he was again shifted to Medical Intensive Care Unit. Cardiology consultation was sought and was managed. In view of suspected hospital-acquired pneumonia, prophylactic treatment of Elores 1.5 g B.D was continued for 5 days. The patient responded to the treatment well, was stable and discharged with follow-up advice. th Keywords: Antibiotic adjuvant entity, Complicated urinary tract infections, Elores, Poly-infection.